지역의 로컬리티 실천현황과 네트워킹 방안 - 정혜숙(Jung Hye-sug) (한국학논집, 2011)
근대성과 중심성에 따른 문제들을 극복하기 위한 탈중심, 탈근대 담론이 확산되면서 그 동안 배제되었던 주체, 대상에 대한 관심이 확산되기 시작하였다. 이는 지역/지방, 소수자, 주변성, 장소성, 탈식민성 등의 개별 영역에 대한 연구뿐만 아니라 중층적이고 복합적으로 발견되는 현상에 대한 연구로도 확산되어지고 있다. 나아가 지역/지방, 로컬리티가 갖고 있는 개별적 특수성을 발견하는 과정에 대한 연구로, 내부 성원들의 삶의 뿌리라 할 수 있는 공동체 복원 혹은 만들기를 위한 자율적이고 능동적인 운동으로까지 확장되고 있다. 이 논문은 로컬에 대한 연구가 어떠한 형태로 구체화되고 실천되어지고 있는지에 대한 현황을 점검해보고자 하는 것이다. 이는 로컬리티가 미리 규정되어지고 있는지에 대한 현황을 점검해보고자 하는 것이다. 이는 로컬리티가 미리 규정되어지는 어떤 것이 아니라 다양한 연구들을 통해 구성되어져 가는 것이기 때문이다. 본 논문에서는 먹거리 중심의 생협운동, 교육영역의 도서관, 생활영역의 풀뿌리자치공동체, 문화영역의 문화공동체를 대상으로 삼았다. 더 많은 풀뿌리활동들이 있지만 아직 초기 단계에 있어 활동내용들이 많지 않거나 정보를 얻을 수 있는 통로가 없어 소개하지 못한 곳도 있으며 시간과 역량부족으로 더 많은 곳의 사례를 포함하지 못한 곳도 있다. 로컬 내에서 활동하는 다양한 풀뿌리 공동체들은 공동체들의 형성, 발전과정 속에서 비슷한 경험을 가지게 되는데 이 때 공동체가 경험한 성공과 실패는 다른 공동체의 발전과정에 모델이 되어준다. 동시에 비슷한 내용으로 기획된 사업이 중복되어 풀뿌리 전체의 역량을 소진하거나 성과를 배가시킬 수 있는 기회를 놓치게 되는 결과를 가져오기도 한다. 따라서 대부분의 풀뿌리 자치운동을 하는 활동가뿐만 아니라 시민사화영역의 단체 활동가, 지역연구자, 전문가들 모두가 네트워킹에 대한 필요와 요구를 가진다. In order to overcome the problems caused by modernity and centrality, postmodern arguments for decentralization have recently been proliferating. Concerns about subject and object have spread not only to individual research projects on locality, minority, circumambiency, ‘placeness’ and decolonization, but also to research into other complex phenomena. As a result, research into the distinctive characteristics of areas is now on the increase, and autonomous and active campaigns for the creation or restoration of communities are multiplying. The purpose of this article is to examine how current research on localities has been concretized and actualized. This is because locality is not predefined but is something composed from a wide variety of research. This article focuses on a living-cooperative association’s food campaign, an educational library, a grass-roots community and a cultural community. There are still more grass-roots community activities to be introduced, but the sources of information are insufficient and the communities’ activities are also not yet mature enough. The successes or failures of one community become a model for other communities since many local grass-roots communities go through similar experiences in the process of their formation and development. Furthermore, it is possible that simultaneous and similar community events are duplicated, resulting in the exhaustion of the overall ability of the grass-roots community to take action or in the communities missing chances to multiply their outcomes. Therefore, there is a clear need for networking among grass-roots community activists, civil-society movement activists, and local researchers and experts. KCI Citation Count: 3